Copyright Protection Against Songs Involving Artificial Intelligence (AI) In the Music Industry Based on Indonesian Copyright Law - Tarigan, Stevani; Martono Anggusti; Roida Nababan (Jurnal Ius Constituendum, 2025)
This writing aims to determine the legal protection of copyright to songs involving Artificial Intelligence in the music industry based on Law Number 28 of 2014 concerning Copyright and who is entitled to ownership of the copyright. The use of Artificial Intelligence technology in the creation of a song and works in other fields is increasing in number which causes disputes over copyright ownership issues to be a concern for musicians, especially in the music industry. Improvement of Indonesian copyright regulation is a special challenge for the Indonesian government to compile a special policy about copyright that uses Artificial Intelligence technology. The method used is normative juridical with statutory and conceptual approaches, as well as analysis of relevant international regulations. The results of the writing show that Artificial Intelligence is considered a tool, not a legal subject, so copyright in works involving Artificial Intelligence is still given to humans who act as initiators or instructors in the creative process. Regulations in Indonesia have not been fully adaptive to the development of Artificial Intelligence, so a review is needed to accommodate this technological innovation. It is recommended that there be cooperation with international organizations such as WIPO to develop harmonious and comprehensive policies for protecting copyright in the digital era.